(3GdeONd Edi Yde GdELJeGY s - (3eMeO eMehO(B, (3GdLhgQjs ((3YeGf (B:s (3OGQ GdeSjQI ddfTQ hGdJhRjYs, 2015)
(3jVe ehVhY GdYde hMOhOg hGdNdGUI GdfXQjI GdeYGUQI aj Yde GdELJeGY, ejGOjf GdOQGSI aj Yde GdELJeGY hYde GdELJeGY GdJWHjbj(B. s
Keywords: (3GdELJeGY, Yde s; (3GdYdhe GdELJeGYjIs